2019
DOI: 10.1111/ijsw.12392
|View full text |Cite
|
Sign up to set email alerts
|

Deservingness in the eye of the beholder: A vignette study on the moderating role of cultural profiles in supporting activation policies

Abstract: People support welfare policy if its beneficiaries are perceived as deserving of support. This study found that individuals’ cultural worldviews play a role in assessing the deservingness of welfare recipients. We investigated whether four different cultural profiles find some beneficiaries to be more deserving than others and how this relates to support for social rights (welfare benefit, retraining, job coach) and obligations (mandatory volunteering). A Dutch vignette experiment showed that reasons for suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…While previous research has investigated how the importance of deservingness criteria varies in accordance with social valuese.g. cultural orientations, humanitarianism or political orientations (Gielens et al, 2019;Hansen, 2018;Petersen et al, 2011) -, the interaction between deservingness and self-interest has received scant attention. However, it is not implausible to assume that, for some social groups, deservingness might matter less than for others, and that therefore both factors interact.…”
Section: Interactions Between Self-interest and Deservingnessmentioning
confidence: 99%
“…While previous research has investigated how the importance of deservingness criteria varies in accordance with social valuese.g. cultural orientations, humanitarianism or political orientations (Gielens et al, 2019;Hansen, 2018;Petersen et al, 2011) -, the interaction between deservingness and self-interest has received scant attention. However, it is not implausible to assume that, for some social groups, deservingness might matter less than for others, and that therefore both factors interact.…”
Section: Interactions Between Self-interest and Deservingnessmentioning
confidence: 99%
“…Applebaum, 2001) suggested that control, reciprocity and identity play crucial role among the model criteria. However, recent studies indicate that the perception of deservingness differs depending both on the characteristics of the respondent and potential beneficiaries of social benefits (Jeene et al, 2013;Meuleman et al, 2020;Gielens et al, 2019). Consequnetly, Heuer and Zimmerman (2020) suggest that one criterion may be used by respondents to justify their assessment of deservingness, both high and low.…”
Section: Carin or Carina? The Criterion Of Adequacymentioning
confidence: 99%
“…There is a broad literature studying the perception of deservingness of welfare beneficiaries (Aarøe & Petersen, 2014;Gielens et al, 2019;Jeene et al, 2013;Petersen, 2011;Reeskens & van der Meer, 2019;van Oorschot, 2006 etc.). Most of the previous studies on deservingness perception are of quantitative nature; rely on a representative population surveys and strive to answer how societies perceive the extent to which different subgroups of citizens are deemed worthy or unworthy of receiving help.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately however, the focus on the dimensionality of policy designs has come at the cost of neglecting the dimensionality of UBI support . In studies of welfare legitimacy, the dimensional structure of attitudes has been leveraged to understand which aspects of welfare policy people distinguish when forming their opinions, such as social rights versus obligations (Achterberg et al, 2014; Gielens et al, 2019) and policy principles versus implementation (Roosma et al, 2013). Similarly, the commonalities in support for different aspects of UBI will show which dimensions the public distinguishes.…”
Section: Introductionmentioning
confidence: 99%